PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) RANTING BANGKINANG - Said Alhudri; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study aims to determine the effect of total quality management on the performance of employees at PT. PLN (Persero) Ranting Bangkinang.Data collected by the data collection techniques through questionnaires and performed simple linear regression analysis using SPSS version 17.Results of research conducted by a simple linear regression analysis on the obtained value of b (regression coefficient) of 0.120 for constanta at 22.149, where an independent variable that any change in the total quality management increased by one unit then it will affect the dependent variable employee performance will suffer keanikan of 0.052, Based on these results it can be concluded that the value of the correlation coefficient has a low value or positive, it means that there is the influence of total quality management on employee performance. While the value of determination (effect) between total quality management on the performance of employees of PT. PLN (Persero) Branch Bangkinang showed significant influence and has a strong relationship level.Keyworsd: Total Quality Management, Kinerja Karyawan